Gilligan and Captain Kirk have more in common than you think: 1960s Camp TV as an alternative genealogy for Cult TV. Issue 1 (1st March 2018) - Phillips, W. D.; Pinedo, Isabel
A number of mid-1960s prime-time television programmes such as Batman (1966–69) and The Monkees (1966–68) seemed to not just allow, but encourage viewing practices that transcended the infantilized conceptualization of that era's television audiences. This article argues such programmes constitute a significant and unhistoricized set of predecessors to contemporary Cult TV. Analysing audience interpretive practices and the set of textual characteristics that facilitated and encouraged such participatory and interpretive activities, we also identify a relatively cohesive group of programmes, all of which premiered in that period, that we retrospectively nominate as 'Camp TV'. These shows' distinguishing narrative elements, namely the surreal humour of Green Acres (1965–71), satire of Get Smart (1965–70), exaggerated clichés of Batman (1966–69) and anarchic character of The Monkees appealed to a youth audience and lent themselves to multiple readings and viewing practices similar to those that would come to greater fruition with the later development of Cult TV.